Analisis Faktor-Faktor yang Mempengaruhi Daya Saing Batik Sekar Jati Ririn Jombang - Widyaningsih, Bekti; Rahma, Varizka Alzana (Universitas KH. A. Wahab Hasbullah, 2022)
In the industrial world, it is closely related to competitiveness, as the times develop, business owners should not be satisfied with the results that have been obtained because business competition is getting tighter. Batik is one of the works of the Indonesian people that needs to be preserved because it has become a hereditary legacy from the previous ancestors. Batik Sekar Jati By Ririn Jombang Regency is one of the largest batik showrooms in Jombang Regency which continues to strive to be able to compete by applying competitiveness factors. This research is a type of qualitative field research using primary data and secondary data, besides that the data collection method in this study uses observation, direct interviews, and documentation methods. Based on the research results from the application of competitiveness in Batik Sekar Jati By Ririn Jombang Regency which was founded in 1993 using three factors: product innovation factors by creating new products that have high selling quality, product quality factors by applying the best production processes, human resource factors by optimizing the performance of each batik craftsman and his employees. The results of the study also concluded that the product innovation factor, product quality factor, human resource factor applied by Batik Sekar Jati By Ririn Jombang Regency has a positive influence in increasing market competitiveness.